Analisis Keruntuhan Lereng pada Jalan Muaradua – Kotabatu, Kabupaten OKU Selatan, Sumatra Selatan - Haris, Ari Daman; Gofar, Nurly (Universitas Kristen Maranatha, 2025)
Infrastructure development leads to the cutting of slope dan additional construction loads on crest. Although the impact of slope cutting and additional construction loads on slope stability has been taken into account, several processes that follow, such as increased pore water pressure caused by rainwater seepage and the occurrence of cracks on the ground surface, can trigger slope failure. This article presents a stability analysis of a natural slope that has been cut to make room for the construction of a new road below the existing road. The stability analysis shows that the slope is in a stable condition before (FoS = 1.694) and after the construction (FoS = 1.423). However, the slope collapsed after heavy rain for 3 days on July 20th – 22nd, 2022. The failure plane starts at the crest of the slope, which is in the middle of the existing road, and ends at the toe. Seepage analysis carried out due to rain infiltration by considering the position of the crack as the starting point of the landslide plane, shows that there is an increase in pore water pressure in the slope, and the FoS decreases to 0.973. Remedial work carried out after a failure includes realigning the existing road, strengthening the toe of the slope with a retaining structure, covering the slope surface with vegetation, and arranging surface drainage.